Percutaneous Versus Open Treatment of Posterior Pelvic Ring Injuries: Changes in Practice Patterns Over Time. Issue 9 (September 2018) - Gire, Jacob D.; Jiang, Sam Y.; Gardner, Michael J.; Bishop, Julius A.
Abstract : Objective: To determine how the utilization of open versus percutaneous treatment of posterior pelvic ring injuries in early-career orthopaedic surgeons has changed over time. Methods: Case log data from surgeons testing in the trauma subspecialty for part II of the American Board of Orthopaedic Surgery examination from 2003 to 2015 were evaluated. Current procedural terminology codes for percutaneous fixation (27216) and open fixation (27218) of the posterior pelvic ring were evaluated using a regression analysis. Results: A total of 377 candidates performed 2095 posterior ring stabilization procedures (1626 percutaneous, 469 open). Total case volume was stable over time [β = −1.7 (1.1), P = 0.14]. There was no significant change in the number of posterior pelvic ring fracture surgery cases performed per candidate per test year [β = 0.1 (0.1), P = 0.50]. The proportion of posterior pelvic ring cases performed percutaneously increased significantly from 49% in 2003 to 79% in 2015 [β = 1.0 (0.4), P = 0.03]. There was a significant decrease in the number of open cases reported per candidate [β = −0.07 (0.03), P = 0.008]. Discussion and Conclusion: Early-career orthopaedic surgeons are performing more percutaneous fixation of the posterior pelvic ring and less open surgery. The impact of this change in volume on surgeon proficiency is unknown and warrants additional research.